2014
DOI: 10.1039/c4tc00897a
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence activity of Ba1−xCaxTiO3: dependence on particle size and morphology

Abstract: Substitution of Ba/Ca (0.25/0.75) in Ba1−xCaxTiO3 compounds causes defects which inhibit the growth of particles and promote higher photoluminescence emission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 63 publications
1
15
0
8
Order By: Relevance
“…Therefore, it can be concluded that the TiO 6 octahedron is preserved. Figure 2a also presents the XPS spectra of O 1   s valence state, which shows one main peak corresponding to oxygen in BaTiO 3 (528.8 eV) and a broad peak caused by chemisorbed species and/or oxygen vacancies (531.9 eV)39. Previously, Lewis Wasson et al 40.…”
Section: Resultsmentioning
confidence: 90%
“…Therefore, it can be concluded that the TiO 6 octahedron is preserved. Figure 2a also presents the XPS spectra of O 1   s valence state, which shows one main peak corresponding to oxygen in BaTiO 3 (528.8 eV) and a broad peak caused by chemisorbed species and/or oxygen vacancies (531.9 eV)39. Previously, Lewis Wasson et al 40.…”
Section: Resultsmentioning
confidence: 90%
“…The scanning electron microscopy image (FE-SEM) of this sample (x¼ 0 -BaTiO 3 ) showed that growth generates nanostructures close to having spherical morphology, whose particle size did not exceed 100 nm. In previous studies [13,14], the growth of BaTiO 3 spherical particles prepared under similar conditions using 6 mol/L KOH as mineralizer was also observed. However, barium carbonate as additional phase was identified and the particle observed by FE-SEM images showed sizes greater than 100 nm.…”
Section: Resultsmentioning
confidence: 68%
“…Neste último caso, estes materiais são chamados Óxidos Perovskitas, com fórmula ABO 3 . As perovskitas mais comuns são aquelas em que A é um cátion de um elemento alcalino e B um metal de transição no mesmo estado de valência Figura 1.…”
unclassified
“…Em muitos casos, esta estrutura favorece a acomodação de uma grande quantidade de defeitos, provocando distorções na rede periódica que podem ser geradas por deslocamentos atômicos, rompimento de simetria, torções sobre ligações, vacâncias iônicas ou catiônicas ou ainda por uma mudança de coordenação local. 2,3 Estes defeitos são responsáveis, portanto, pelo grau de ordenamento estrutural apresentado por estes materiais e podem valorizar algumas propriedades ou promoverem outras, como a fotoluminescência em temperatura ambiente, exibidas pelos titanatos. Portanto, o conhecimento das propriedades intrínsecas de titanatos é relevante e estas podem ser modificadas durante o seu processamento através do uso de diferentes técnicas de síntese e de dopagem controlada.…”
unclassified
See 1 more Smart Citation